2007
DOI: 10.3390/12122599
|View full text |Cite
|
Sign up to set email alerts
|

Two New Triterpenoids from Photinia serrulata

Abstract: Abstract:Two new triterpenoids, 2α,3β,11α,13β-tetrahydroxy-12-ketooleanan-28-oic acid (1) and 3β-hydroxy-12-keto-9(11)-ursen-28,13β-olide (2) were isolated from the leaves of Photinia serrulata. Their structures were identified by spectral methods. Compounds 1 and 2 were assessed for cytotoxic activity against three human tumor cell lines (A-549, HCT-8, and BEL-7402), and they showed no cytotoxic effects at concentrations up to 5μg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Its tender leaves are used as edible vegetables in the south of China, and the matured leaves are used for the treatment of the above diseases 4 . It has been reported that the leaves of P. serratifolia contain essential oils, triterpenoids, flavonoids, polyphenols, and other bioactive compounds, which have been demonstrated to have antioxidant and anticancer activities in vitro 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its tender leaves are used as edible vegetables in the south of China, and the matured leaves are used for the treatment of the above diseases 4 . It has been reported that the leaves of P. serratifolia contain essential oils, triterpenoids, flavonoids, polyphenols, and other bioactive compounds, which have been demonstrated to have antioxidant and anticancer activities in vitro 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Its tender leaves are used as edible vegetables in the south of China, and the matured leaves are used for the treatment of the above diseases 4 . It has been reported that the leaves of P. serratifolia contain essential oils, triterpenoids, flavonoids, polyphenols, and other bioactive compounds, which have been demonstrated to have antioxidant and anticancer activities in vitro 4,5 .The boundaries of some species have not been clearly defined in Rosaceae family due to similar morphological features exhibiting among Rosaceae species 1 . Compared with morphological identification, DNA sequences can produce more accurate phylogenetic relationships 1,6 .…”
mentioning
confidence: 99%
“…Phytochemical research showed that triterpenoids and cyanophoric glycosides, for example, ursane triterpenoids and analogs, ursolic acid, oleanolic acid, prunasin, and saponin, were the main compounds in the leaves of P. serrulata [2][3][4][5][6][7]. Pharmacological investigations showed that the leaves of P. serrulata are toxic, possess antioxidant and antibacterial activity, can kill Tetranychus cinnabarinus and can suppress plant growth [6][7][8][9][10][11]. No research has so far been conducted concerning the chemical constituents of the essential oil of the flowers.…”
mentioning
confidence: 99%